2001
DOI: 10.1007/s004360000316
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of the eurasian badger ( Meles meles L.) in Spain: a biogeographic approach

Abstract: Eighty-five Eurasian badgers, Meles meles (Linnaeus, 1758), from four mainland biogeographic Spanish areas were analysed for helminths. Seventeen helminth species were found: Brachylaima sp., Euparyphium melis and Euryhelmis squamula (Trematoda), Atriotaenia incisa and Mesocestoides sp. (Cestoda) and Aelurostrongylus pridhami, Angiostrongylus vasorum, Aonchotheca putorii, Crenosoma melesi, Mastophorus muris, Molineus patens, Pearsonema plica, Physaloptera sibirica, Strongyloides sp., Trichinella sp., Uncinaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
3
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 20 publications
(32 reference statements)
7
85
3
5
Order By: Relevance
“…Physaloptera sibirica has been recently reported by Torres et al (2001) parasitizing other mustelid species as M. meles in the Iberian Peninsula. Its distribution seems to be limited to geographical areas of high altitude and cold climate, as it was similarly apparent in other Spanish studies in which the species was found parasitizing foxes (Miquel et al 1996, Segovia et al 2004.…”
Section: Faunistic Analysismentioning
confidence: 99%
“…Physaloptera sibirica has been recently reported by Torres et al (2001) parasitizing other mustelid species as M. meles in the Iberian Peninsula. Its distribution seems to be limited to geographical areas of high altitude and cold climate, as it was similarly apparent in other Spanish studies in which the species was found parasitizing foxes (Miquel et al 1996, Segovia et al 2004.…”
Section: Faunistic Analysismentioning
confidence: 99%
“…4,26 Natural infection has also rarely been reported in other species including Eurasian badgers (Meles meles), wolves (Canis lupus), and a coyote (Canis latrans). 6,28,33 The life cycle of A. vasorum is indirect. Gastropods (aquatic and terrestrial snails, slugs) most frequently serve as intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Angiostrongylus vasorum is a metastrongyloid nematode that is known to cause cardiopulmonary disease in dogs, foxes, and other canids, with reports in a few other species, including Eurasian badgers. 1,2,5,11,14,16 Its geographical distribution is patchy but appears to be expanding in several parts of the world, 13 and surveys of foxes reveal the parasite to be currently endemic in much of the southern half of the United Kingdom, 14 with cases in dogs recently appearing in Bristol (unpublished data). In Copenhagen, also in an endemic area, fatal disease has been reported in several red pandas in the city's zoo in recent years (Grøndahl C Ovoviviparous female worms are located in the cardiac right ventricle and pulmonary vasculature, depositing eggs that pass via the blood to the lungs.…”
mentioning
confidence: 99%